1999
DOI: 10.2165/00007256-199927060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of Common Tendinopathies

Abstract: Tendon disorders are a major problem for participants in competitive and recreational sports. To try to determine whether the histopathology underlying these conditions explains why they often prove recalcitrant to treatment, we reviewed studies of the histopathology of sports-related, symptomatic Achilles, patellar, extensor carpi radialis brevis and rotator cuff tendons. The literature indicates that healthy tendons appear glistening white to the naked eye and microscopy reveals a hierarchical arrangement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
257
0
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 848 publications
(284 citation statements)
references
References 110 publications
7
257
0
20
Order By: Relevance
“…Presence of neovascularization is well documented in advanced tendinopathies and can be demonstrated using Doppler Ultrasound examination [20,22,23,24,25,26]. Similarly, in our study the presence of neovascularization of the LHBT was confirmed in 78% of specimens.…”
Section: Discussionsupporting
confidence: 82%
“…Presence of neovascularization is well documented in advanced tendinopathies and can be demonstrated using Doppler Ultrasound examination [20,22,23,24,25,26]. Similarly, in our study the presence of neovascularization of the LHBT was confirmed in 78% of specimens.…”
Section: Discussionsupporting
confidence: 82%
“…Commonly affected areas include the Achilles, 1 posterior tibialis, [3][4][5][6] patellar, 7,8 lateral elbow, 10 and rotator-cuff tendons. 11,12 The Achilles tendon is the most commonly affected lower extremity structure, with a cumulative lifetime incidence of 5.9% 1 in an inactive population and 50% in elite endurance athletes. 1 The patellar tendon, involved in "jumper's knee," is affected 12% of elite athletes among an assortment of sports, and injury incidence may be as high as 40% in jumping sports such as basketball and volleyball.…”
mentioning
confidence: 99%
“…Os tendões normais são brilhantes, brancos e possuem uma textura fibroelástica, o que demonstra uma grande resistência a cargas mecânicas (KHAN et al, 1999;JÓZSA & KANNUS, 1997; MCNEILLY et al, 1996;STOLINSKI, 1995; BIRK & TRELSTAD, 1986 PARIZOTTO, 1998; REDDY et al, 1998a, b; GUM et al, 1997; ENWEMEKA, 1991a, b;ENWEMEKA et al, 1990; ENWEMEKA, 1989b 2) Fase Neoangiogênica e Proliferativa;…”
Section: I6 Tendãounclassified
“…Os tendões normais são brilhantes, brancos e possuem uma textura fibroelástica, o que demonstra uma grande resistência a cargas mecânicas (KHAN et al, 1999;JÓZSA & KANNUS, 1997;MCNEILLY et al, 1996;STOLINSKI, 1995;BIRK & TRELSTAD, 1986 A ruptura do tendão do calcâneo normalmente é precedida por alterações degenerativas onde há redução do fluxo sanguineo para o tendão com resultante hipóxia local. A alteração da nutrição e da atividade metabólica também predispõem a essas alterações (ALMEKINDERS & DEOL, 1999;SALOMÃO et al, 1993).…”
Section: I6 Tendãounclassified
See 1 more Smart Citation